Method for plugging and optimizing coal rock middle layer structure pores
By using standard liquid prepared by mine water to enter the coal rock into the internal formation of complex-seeding materials, the problem of difficulty in blocking the pores of the medium-layer structure of coal rock in the existing technology is solved, and effective sealing of the deep pore network of coal rock and improving the stability of coal rock is achieved.
Patent Information
- Application Number
- CN202411979581.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The prior art is difficult to effectively block pores in the middle-layer structure of coal rock, resulting in increased risk of coal rock damage and air leakage.
Mine water is used as the base material, and standard liquid A and standard B are prepared to enter the coal rock, respectively, and complex-seeding materials are generated, thereby optimizing the sealing of the deep pore network of coal rock.
Effective sealing of the deep pore network of coal rock has been achieved, new cracks have been reduced, and the integrity and stability of coal rock have been enhanced.
Smart Images

Figure CN119880548A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal rock layer reinforcement, and in particular to a method for sealing and optimizing structural pores in a coal rock middle layer. Background Art
[0002] In my country's primary energy production and consumption structure, coal occupies a dominant position. With the continuous optimization of the primary energy consumption structure, although the proportion of coal continues to decline, the total amount is still growing.
[0003] During the coal mining process, coal roadway excavation and drilling along the layers will induce stress concentration, which will lead to damage to the coal rock and form cracks, which will gradually expand to form a crack network, which may cause leaky air and oxygen pipelines, increasing the risk. In addition, due to the continuous erosion of mine water, the risk of water seepage and water penetration accidents gradually increases.
[0004] At this stage, in order to solve the above problems, the patent with application number CN202210182908.3 discloses "a toughened spray-coated air-tight material and its construction process". The material is composed of calcium oxide, silicon dioxide, aluminum oxide, iron oxide, swelling agent, flame retardant, polymer emulsion and water. It is sprayed on the surface of coal rock, metal, wood, etc., and efficiently bonds to seal surface cracks, block air leakage, and isolate air. The patent with application number CN202111294595.2 discloses a paste quick-setting material for coal rock crack-pore consolidation and its preparation method. The material is a fast-strengthening solidifying material with a short setting time and easy accumulation and forming in plugging coal rock cracks.
[0005] Although the above patent has repaired the fracture network of coal rock layers to a certain extent and reduced the permeability of coal rock. However, coal rock is a porous material, and micropores and mesopores are the main adsorption sites for gases and liquids, and fractures mainly serve as migration channels for fluids in coal rock. These plugging materials, such as concrete slurry and polymer emulsion coatings, each have their own shortcomings. Among them, concrete slurry has a high density and a high viscosity coefficient, and it is difficult to penetrate the deep fracture structure of coal rock. If the grouting pressure is increased, a new fracture network may be formed. Polymer emulsion coatings can often only form a solidified layer on the surface of the coal rock, and they still cannot block and optimize the fracture network from the internal structure of the coal. Therefore, it is necessary to provide a method for blocking and optimizing the pores in the middle structure of coal rock to solve the above technical problems. Summary of the invention
[0006] The purpose of this application is to provide a method for sealing and optimizing the pores in the middle layer structure of coal rock, using mine water as a base material, reducing the physical and chemical erosion of coal rock by mine water while overcoming the problem that the existing sealing base material cannot penetrate deep into the pore network inside the coal rock for sealing, so as to solve or alleviate the problems existing in the above-mentioned prior art.
[0007] In order to achieve the above objectives, this application provides the following technical solutions:
[0008] A method for plugging and optimizing the pores in the coal rock middle layer structure comprises the following steps:
[0009] (1) Pretreatment: grinding the surface of the coal sample and drying the ground coal sample;
[0010] (2) preparing standard solution A and standard solution B, adding additive A to mine water to prepare standard solution A; adding additive B to deionized water to prepare standard solution B;
[0011] (3) Take out the coal sample dried in step (1), place it in a vacuum saturation device filled with standard A liquid, and let it stand for 4 to 6 hours. Observe that no bubbles overflow from the liquid surface within 30 seconds, close the vacuum saturation device, take out the saturated sample, wipe off the surface liquid, and place it in a cool place to stand;
[0012] (4) Place the sample after standing in a cool place in step (3) in a holder and drip standard liquid B into both ends of the holder. When no liquid flows out of the liquid outlet tube within 1 minute, wipe off the liquid on the surface. Repeat 2 to 3 times and then place in a cool place to stand.
[0013] Preferably, in step (1), the ground coal sample is placed in a drying oven and dried at 60° C. for 4 to 8 hours.
[0014] Preferably, in step (2), the additive A is one or more of potassium sulfate, calcium chloride, magnesium chloride, and sodium bicarbonate. The main function of the standard A solution is to balance the original ions in the mine water and increase the electrolysis degree of the original mine water solution.
[0015] Further preferably, the mass ratio of the additive A to the mine water is 1:10-15.
[0016] Preferably, in step (2), the additive B is one or more of magnesium sulfate, sodium bicarbonate, sodium silicate, ethylenediamine, tartaric acid, aluminic acid, sodium chloride, and sodium sulfate. Standard B liquid, as an infiltration crystallization liquid, can quickly react with standard A liquid to generate 3CaO·Al2O3·3CaSO4·32H2O complex precipitate after entering the pore structure filled with standard A liquid, thereby blocking and optimizing the internal fracture network. Among them, magnesium sulfate, sodium bicarbonate, sodium chloride, and sodium sulfate provide the main raw materials for infiltration crystallization reaction with standard A liquid, while ethylenediamine, tartaric acid, and aluminic acid, as chelating agents, can adhere to the surface of the complex precipitate, causing electrostatic action of negative charge sites on the surface of sodium ions, potassium ions, and magnesium ions on the complex precipitate, thereby forming an adsorption layer on the surface of the precipitate. It can also change the ion distribution of sodium ions, potassium ions, silicate ions, etc. on the surface of the complex precipitate, thereby changing the growth direction of the complex precipitate, making it close to columnar crystals and more evenly distributed in the pore network of coal rock.
[0017] Further preferably, the mass ratio of the additive B to deionized water is 1:10-15.
[0018] Preferably, in step (3), the coal sample dried in step (1) is taken out and placed in a ZK-270 vacuum saturation device filled with standard A liquid, the temperature in the vacuum saturation device is 20-30°C, the suction rate is 1±0.2L / S and the vacuum degree is 0-0.1MPa, and the sample is allowed to stand for 4-6 hours. It is observed that no bubbles overflow from the liquid surface within 30 seconds, and the vacuum saturation device is turned off. The saturated sample is taken out, the surface liquid is wiped dry, and the sample is placed in a cool place at 15-23°C for 1-2 hours.
[0019] Preferably, in step (4), the sample after standing in a cool place in step (3) is placed in a TY-5A holder, and standard B liquid is dripped into both ends of the holder. When no liquid flows out of the liquid outlet tube within 1 minute, the liquid on the surface is wiped off, and the process is repeated 2 to 3 times. The sample is then placed in a cool place at 15 to 23°C and allowed to stand for 2 to 3 hours.
[0020] Beneficial effects:
[0021] (1) Compared with the traditional method, the present invention uses a smaller pressure at a pressure slightly higher than normal pressure to ensure that the coal sample maintains integrity during the test while minimizing the appearance of new cracks. The solvents of standard liquid A and standard liquid B are mine water and deionized water, respectively, to ensure that standard liquid A and standard liquid B have lower viscosity resistance in coal rock, so that they have stronger penetration performance and can penetrate deep cracks in coal samples.
[0022] (2) The traditional direct grouting method is to directly inject the pre-made slurry into the coal sample or spray it on the surface of the coal sample by pressurizing. The plugging principle is to plug from the outside to the inside, so the slurry cannot enter the deep fracture network of the coal rock for solidification and plugging. The step-by-step liquid injection method adopted by the present invention allows the standard A liquid and the standard B liquid to enter the interior of the specimen respectively. The standard A liquid and the standard B liquid generate complex-precipitate in the pore network inside the coal rock, and optimize the plugging of the deep pore network of the coal rock from the inside, which fundamentally solves the problem instead of forming a solidified layer on the surface of the coal sample for a short time.
[0023] (3) The present invention uses mine water as the base material, which reduces the content of mine water in the underground mine, thereby reducing the physical and chemical effects of mine water on coal rock erosion, and further enhances the integrity and stability of the coal rock. In addition, the remaining mine water in the experiment can be recycled, avoiding the complexity of making slurry, making the plugging optimization process more convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. Among them:
[0025] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0026] The present application will be described in detail below with reference to the accompanying drawings and in conjunction with embodiments. Each example is provided by way of explanation of the present application and does not limit the present application. In fact, it will be clear to those skilled in the art that modifications and variations may be made in the present application without departing from the scope or spirit of the present application. For example, a feature shown or described as a part of an embodiment may be used in another embodiment to produce yet another embodiment. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the embodiments of the present invention should belong to the scope of protection of the embodiments of the present invention.
[0027] A method for plugging and optimizing the pores in the coal rock middle layer structure comprises the following steps:
[0028] (1) Pretreatment: Grind the surface of the coal sample and place the polished coal sample in a drying oven and dry it at 60°C for 4 to 8 hours.
[0029] (2) Prepare standard A solution and B solution, add additive A to the mine water to prepare standard A solution; additive A is one or more of potassium sulfate, calcium chloride, magnesium chloride, and sodium bicarbonate, and the mass ratio of additive A to mine water is 1:10-15. The main function of standard A solution is to balance the original ions in the mine water and increase the electrolysis degree of the original mine water solution.
[0030] Additive B is added to deionized water to prepare standard B solution; additive B is one or more of magnesium sulfate, sodium bicarbonate, sodium silicate, ethylenediamine, tartaric acid, aluminic acid, sodium chloride, and sodium sulfate. The mass ratio of additive B to deionized water is 1:10-15. Standard B solution, as an infiltration crystallization liquid, can quickly react with standard A solution to generate 3CaO·Al2O3·3CaSO4·32H2O complex precipitate after entering the pore structure filled with standard A solution, thereby blocking and optimizing the internal fracture network. Among them, magnesium sulfate, sodium bicarbonate, sodium chloride, and sodium sulfate provide the main raw materials for infiltration crystallization reaction with standard A solution, while ethylenediamine, tartaric acid, and aluminic acid, as chelating agents, can adhere to the surface of the complex precipitate, causing electrostatic action of the negative charge sites on the surface of the complex precipitate with sodium ions, potassium ions, and magnesium ions, thereby forming an adsorption layer on the surface of the precipitate. It can also change the ion distribution of sodium ions, potassium ions, silicate ions, etc. on the surface of the complex precipitate, thereby changing the growth direction of the complex precipitate, making it closer to columnar crystals and more evenly distributed in the pore network of the coal rock.
[0031] (3) Take out the coal sample dried in step (1), place it in a ZK-270 vacuum saturation device filled with standard A liquid, the temperature in the vacuum saturation device is 20-30°C, the suction rate is 1±0.2L / S and the vacuum degree is 0-0.1MPa, let it stand for 4-6 hours, observe that no bubbles overflow from the liquid surface within 30 seconds, turn off the vacuum saturation device, take out the saturated sample, wipe off the surface liquid and place it in a cool place at 15-23°C for 1-2 hours.
[0032] (4) Place the sample after standing in a cool place in step (3) in a TY-5A holder, and drip standard B liquid into both ends of the holder. When no liquid flows out of the liquid outlet tube within 1 minute, wipe off the liquid on the surface. Repeat 2 to 3 times and place in a cool place at 15 to 23°C for 2 to 3 hours.
[0033] Example 1
[0034] A method for plugging and optimizing the pores in the coal rock middle layer structure comprises the following steps:
[0035] (1) Pretreatment: The surface of the coal sample is polished and then placed in a drying oven for drying at 60°C for 4 to 8 hours.
[0036] (2) preparing standard solution A and standard solution B, adding additive A to mine water to prepare standard solution A, wherein the standard solution A comprises 92.5 wt % of mine water, 1.5 wt % of potassium sulfate, 2.3 wt % of calcium chloride, 1.7 wt % of magnesium chloride, and 2 wt % of sodium bicarbonate;
[0037] Add additive B to deionized water to prepare standard B solution; wherein the components of standard B solution include 91.8wt% deionized water, 0.8wt% magnesium sulfate, 1.3wt% sodium silicate, 2.4wt% sodium chloride, 0.2wt% sodium aluminate, 0.1wt% tartaric acid, 0.3wt% ethylenediamine, 1.7wt% sodium bicarbonate, and 1.4wt% sodium sulfate.
[0038] (3) Take out the dried coal sample and place it in a ZK-270 vacuum saturation device filled with standard A liquid, and ensure that the temperature in the vacuum saturation device is between 20 and 30°C, the air extraction rate is about 1L / S (between 0.9 and 1L / S), and the vacuum degree is between 0 and 0.1MPa. Place the coal sample in the vacuum saturation device for 4 to 6 hours. When no bubbles overflow from the liquid surface within 30 seconds, close the vacuum saturation device. Take out the saturated sample, wipe off the surface liquid, and place it in a cool place at 15 to 23°C for 1 to 2 hours.
[0039] (4) Place the sample after standing in a cool place in step (3) in a TY-5A holder (hereinafter referred to as the holder), drip standard B liquid into both ends of the holder, and when no liquid flows out of the liquid outlet tube within 1 minute, close the device and wipe off the liquid on the surface. Repeat 2 to 3 times, then place in a cool place at 15 to 23°C for 2 to 3 hours. The flow chart is as follows Figure 1 shown.
[0040] Comparative Example 1
[0041] A method for plugging and optimizing the pores in the coal rock middle layer structure comprises the following steps:
[0042] (1) Pretreatment: The surface of the coal sample is polished and then placed in a drying oven for drying at 60°C for 4 to 8 hours.
[0043] (2) Take out the dried coal sample and place it in a ZK-270 vacuum saturation device filled with mine water, and ensure that the temperature in the device is maintained between 20 and 30°C, the air extraction rate is about 1L / S, and the vacuum degree is between 0 and 0.1MPa. Let it stand for 4 to 6 hours. When no bubbles overflow from the liquid surface within 30 seconds, turn off the vacuum saturation device. Take out the saturated sample, wipe off the surface liquid and place it in a cool place for 1 to 2 hours.
[0044] (3) Place the sample in the holder and drip deionized water solution into both ends of the TY-5A holder (hereinafter referred to as the holder). When no liquid flows out of the outlet tube within 1 minute, close the device and wipe off the liquid on the surface. Repeat 2 to 3 times and then place in a cool place at 15 to 23°C for 2 to 3 hours.
[0045] Comparative Example 2
[0046] A method for plugging and optimizing the pores in the coal rock middle layer structure comprises the following steps:
[0047] (1) Pretreatment: The surface of the coal sample is polished and then placed in a drying oven for drying at 60°C for 4 to 8 hours.
[0048] (2) preparing standard solution A and standard solution B, adding additive A to mine water to prepare standard solution A, wherein the standard solution A comprises 92.5 wt % of mine water, 1.5 wt % of potassium sulfate, 2.3 wt % of calcium chloride, 1.7 wt % of magnesium chloride, and 2 wt % of sodium bicarbonate;
[0049] (3) Take out the dried coal sample and place it in a ZK-270 vacuum saturation device filled with standard A liquid, and ensure that the temperature in the device is maintained between 20 and 30°C, the air extraction rate is about 1L / S, and the vacuum degree is between 0 and 0.1MPa. Let it stand for 4 to 6 hours. When no bubbles overflow from the liquid surface within 30 seconds, turn off the vacuum saturation device. Take out the saturated sample, wipe off the surface liquid and place it in a cool place at 15 to 23°C for 1 to 2 hours.
[0050] (4) Place the sample in the holder and drip deionized water solution into both ends of the TY-5A holder (hereinafter referred to as the holder). When no liquid flows out of the outlet tube within 1 minute, close the device and wipe off the liquid on the surface. Repeat 2 to 3 times and then place in a cool place at 15 to 23°C for 2 to 3 hours.
[0051] Comparative Example 3
[0052] A method for plugging and optimizing the pores in the coal rock middle layer structure comprises the following steps:
[0053] (1) Pretreatment: The surface of the coal sample is polished and then placed in a drying oven for drying at 60°C for 4 to 8 hours.
[0054] (2) Adding additive B to deionized water to prepare standard solution B; wherein the components of standard solution B include 91.8wt% of deionized water, 0.8wt% of magnesium sulfate, 1.3wt% of sodium silicate, 2.4wt% of sodium chloride, 0.2wt% of sodium aluminate, 0.1wt% of tartaric acid, 0.3wt% of ethylenediamine, 1.7wt% of sodium bicarbonate, and 1.4wt% of sodium sulfate.
[0055] (3) Take out the dried coal sample and place it in a ZK-270 vacuum saturation device filled with mine water solution, and ensure that the temperature in the device is maintained between 20 and 30°C, the air extraction rate is about 1L / S and the vacuum degree is between 0 and 0.1MPa. Let it stand for 4 to 6 hours. When no bubbles overflow from the liquid surface within 30 seconds, turn off the vacuum saturation device. Take out the saturated sample, wipe off the surface liquid and place it in a cool place at 15 to 23°C for 1 to 2 hours.
[0056] (4) Place the sample in the holder and drip standard liquid B into both ends of the TY-5A holder (hereinafter referred to as the holder). When no more liquid flows out of the outlet tube within 1 minute, close the device and wipe off the liquid on the surface. Repeat 2 to 3 times and then place in a cool place at 15 to 23°C for 2 to 3 hours.
[0057] Detection and analysis
[0058] The results of the above-mentioned embodiments and comparative examples were tested and the permeability results are shown in Table 1.
[0059] Table 1 Test results of embodiments and comparative examples
[0060]
[0061] In Comparative Example 1, the liquid placed in the vacuum saturation device is mine water, and the liquid used for the drip seepage test is deionized water.
[0062] Compared with Comparative Example 1, Comparative Example 2 changes the type of liquid placed in the vacuum saturation device (standard A liquid). As shown in Table 1, the vacuum saturation time of Comparative Example 2 is significantly reduced compared with Comparative Example 1, the permeability of Comparative Example 2 decreases by about 32.41% relative to Comparative Example 1, and the porosity decreases by about 18.34% relative to Comparative Example 1.
[0063] Comparative Example 3 changes the type of liquid used for dripping (standard liquid B). As shown in Table 1, compared with Comparative Example 1, the vacuum saturation time of Comparative Example 3 is not significantly shortened, but the time used for its dripping test is significantly reduced, the permeability decreases by about 32.25%, and the porosity decreases by about 15.52%.
[0064] Compared with Comparative Example 1, Example 1 changes the type of liquid placed in the vacuum saturation device (standard A liquid) and the type of liquid used for the dripping test (standard B liquid). As shown in Table 1, compared with Comparative Example 1, both the vacuum saturation time and the time used for the dripping test in Example 1 are greatly reduced, and the reduction in permeability of Example 1 is about 77.78%, and the reduction in porosity is about 50.97%, which is obviously better than that in the comparative example. Therefore, the method for plugging and optimizing the pores in the middle layer structure of coal rock provided by the present invention can generate complex precipitates from the inside without destroying the external pore network of coal rock, thereby achieving a better plugging effect.
[0065] The present invention adopts a step-by-step liquid injection method to allow standard liquid A and standard liquid B to enter the interior of the test piece respectively. Standard liquid A and standard liquid B generate complex-precipitate in the pore network inside the coal rock, completing the optimization and plugging of the deep pore network of the coal rock from the inside, fundamentally solving the problem, rather than forming a short-term solidified layer on the surface of the coal sample.
[0066] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0067] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for plugging and optimizing the pores in the middle layer structure of coal rock, characterized in that: The following steps are involved: (1) Pretreatment: grinding the surface of the coal sample and drying the ground coal sample; (2) preparing standard solution A and standard solution B, adding additive A to mine water to prepare standard solution A; adding additive B to deionized water to prepare standard solution B; (3) Take out the coal sample dried in step (1), place it in a vacuum saturation device filled with standard A liquid, and let it stand for 4 to 6 hours. Observe that no bubbles overflow from the liquid surface within 30 seconds, close the vacuum saturation device, take out the saturated sample, wipe off the surface liquid, and place it in a cool place to stand; (4) Place the sample after standing in a cool place in step (3) in a holder and drip standard liquid B into both ends of the holder. When no liquid flows out of the liquid outlet tube within 1 minute, wipe off the liquid on the surface. Repeat 2 to 3 times and then place in a cool place to stand.
2. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 1 is characterized in that: In step (1), the ground coal sample is placed in a drying oven and dried at 60° C. for 4 to 8 hours.
3. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 1 is characterized in that: In step (2), the additive A is one or more of potassium sulfate, calcium chloride, magnesium chloride, and sodium bicarbonate.
4. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 3 is characterized in that: The mass ratio of the additive A to the mine water is 1:10-15.
5. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 1 is characterized in that: In step (2), the additive B is one or more of magnesium sulfate, sodium bicarbonate, sodium silicate, ethylenediamine, tartaric acid, aluminic acid, sodium chloride, and sodium sulfate.
6. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 5 is characterized in that: The mass ratio of the additive B to deionized water is 1:10-15.
7. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 1, characterized in that: In step (3), take out the coal sample dried in step (1), place it in a ZK-270 vacuum saturation device filled with standard A liquid, the temperature in the vacuum saturation device is 20-30°C, the suction rate is 1±0.2L / S and the vacuum degree is 0-0.1MPa, let it stand for 4-6 hours, observe that no bubbles overflow from the liquid surface within 30 seconds, turn off the vacuum saturation device, take out the saturated sample, wipe off the surface liquid and place it in a cool place at 15-23°C for 1-2 hours.
8. The method for blocking and optimizing the pores in the coal rock middle layer structure according to claim 1 is characterized in that: In step (4), the sample after standing in a cool place in step (3) is placed in a TY-5A holder, and standard B liquid is dripped into both ends of the holder. When no liquid flows out of the liquid outlet tube within 1 minute, the liquid on the surface is wiped off. After repeating 2 to 3 times, the sample is placed in a cool place at 15 to 23°C and allowed to stand for 2 to 3 hours.
Citation Information
Patent Citations
Paste fluid quick-setting material for coal rock crack-pore consolidation and preparation method of paste fluid quick-setting material
CN114014621A
Toughening type spraying air leakage stopping sealing material and construction technology thereof
CN114806230A
Experimental system for simulating solid-phase particles to plug coal (rock) cracks
CN102587889A
High-freezing-resistance fly ash cement and preparation method thereof
CN116621538A
High-temperature-resistant and high-salt-resistant inorganic precipitation type blocking agent and preparation method thereof
CN116925716A